THREE-DIMENSIONAL NUMERICAL HYDRODYNAMICAL SIMULATION OF LOW/HARD AND HIGH/SOFT STATES IN ACCRETION DISCS OF MICROQUASARS AND QUASARS ON BASE OF UNDEFINED PRECESSION - Nazarenko, V. V.; Nazarenko, S. V. (Одеські астрономічні публікації, 2016)
In this study, the models of slaved precession of accretion disc and donors radiationdriven wind were performed using three-dimensional numerical astrophysical methods by the example of microquasar Cyg X-1. As is shown, in the course of precession of the accretion disc blown by the donor’s wind the states with high and low temperature (low and high mass accretion rate, respectively) start being generated in the centre of disc. Our computations of disc precession performed on base of undefined precession that means each point of rotation axis of accretion disc makes unclosed difficult curve instead of a circle as it is in case of definite precession. In this case, the transition between states of high and low temperature takes place irregularly and not depend on precession period. The duration of transition between these both states is less than intervals of states on several orders of magnitudes